Evaluation of The Impact Delay Payments on The Performance of Subcontractors - Sulung, Anggita Putri (Green Publisher Indonesia, 2025)
Delayed payments in construction projects remain a persistent issue that directly impacts subcontractor performance, causing project timelines, quality, and financial sustainability disruptions. Despite the critical role of subcontractors, empirical research analyzing the influence of owner and contractor financial management on subcontractor performance, particularly moderated by payment delays, is still limited in Indonesia. This study aims to examine the effects of owner and contractor financial management on subcontractor performance, while evaluating the moderating role of payment delays. A quantitative approach was employed, collecting primary data through questionnaires distributed to 34 respondents involved in construction projects across Java and Lampung. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that owner financial management significantly affects subcontractor performance, whereas contractor financial management shows no significant impact. Payment delays significantly moderate the relationship between contractor financial management and subcontractor performance, but have no significant moderating effect on the relationship with owner financial management. These findings highlight the necessity for robust financial management practices and timely payment processes to enhance subcontractor performance. The study offers practical implications for project stakeholders to develop better payment and financial strategies, thereby improving project efficiency and subcontractor sustainability.